Cool-Tether: Energy Efficient On-the-fly WiFi Hot-spots using Mobile Phones - Navda, Vishnu; Ramjee, Ramachandran; Belding, Elizabeth; Padmanabhan, Venkat (International Conference on emerging Networking EXperiments and Technologies (CoNEXT), 2009)
We consider the problem of providing ubiquitous yet affordable Internet connectivity to devices at home, at work, and on the move. In this context, we take advantage of two significant technology trends: the commoditization of WiFi WLAN technology and the rapid growth of cellular data services. We propose an architecture called Cool-Tether that harnesses the cellular radio links of one or more mobile smartphones in the vicinity, builds a WiFi hotspot on-the-fly, and provides energy-efficient, affordable connectivity. Prior approaches to supporting such a tethered mode operation have relied on the WiFi ad hoc mode, which impedes the key goal of conserving battery energy on mobile phones. To address the challenges of energy efficiency, Cool-Tether carefully optimizes the energy drain of the WAN (GPRS/ EDGE/ 3G) and WiFi radios on smartphones. In particular, Cool-Tether employs a cloud based gatherer and an energy-aware striper that exploit the unique energy characteristics of the WAN radio. Cool-Tether also uses a novel reverse-infrastructure mode for WiFi, where the client host serves as a WiFi access point while the mobile phone gateway serves as a WiFi client. We prototype Cool-Tether on smartphones and, experimentally demonstrate savings in energy consumption between 38%-71% compared to prior energy-agnostic solutions.